2014
DOI: 10.1016/j.jmateco.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Deadlines in stochastic contests

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…In a very general setting, they characterize the optimal prize structure and find that with convex costs and risk-averse agents, multiple prizes are optimal. Lang, Seel, and Strack (2014) is related to our result about the optimal contest length T . They consider a two-player FPC where agents exert effort over time and breakthroughs arrive according to a Poisson process.…”
Section: Related Literaturesupporting
confidence: 63%
“…In a very general setting, they characterize the optimal prize structure and find that with convex costs and risk-averse agents, multiple prizes are optimal. Lang, Seel, and Strack (2014) is related to our result about the optimal contest length T . They consider a two-player FPC where agents exert effort over time and breakthroughs arrive according to a Poisson process.…”
Section: Related Literaturesupporting
confidence: 63%
“…However, some authors observed different results. Lang et al (2014) argued that a shorter duration reduces solvers' solving time, but increases the intensity of the contest in solvers, noting that seekers can achieve higher returns in a shorter period of time [22]. Dong et al (2016) used data from Taskcn.com and analyzed the impact of task duration on the performance of crowdsourcing contests, finding that with increases in task duration, the effort costs of solvers became higher than the rewards, thereby reducing the number of submissions [23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…If, on the other hand, cost functions are convex, it may be optimal to offer multiple prizes. Lang et al (2014) consider a two-player, fixed-price contest where sellers exert effort over time and breakthroughs arrive according to a Poisson process. The seller with the most breakthroughs wins.…”
Section: Related Literaturementioning
confidence: 99%